Prevalence of anterolateral complex injury and associated injuries in knees with acute complete and partial anterior cruciate ligament injury - Esin Polat, Ayse; Gurpinar, Tahsin; Aydin, Deniz; Polat, Baris; Ozmanevra, Ramadan; Alp Dirik, Mehmet; Erler, Kaan (Annals of Medical Research, 2021)
Aim: Kaplan fibers, Anterolateral capsule, Anterolateral ligament (ALL) and Iliotibial band are defined as secondary stabilizers of the internal tibial rotation of the knee. These structures have been summarized as the "Anterolateral complex" (ALC). We aimed to determine the ALC injury prevalence and the association between Anterior cruciate ligament (ACL) and ALC injury patterns. Materials and Methods: MRI scans of ACL injuries were retrospectively evaluated for the presence of the ACL injury pattern (partial or complete), ALL, iliotibial band, Kaplans fiber, meniscus, bone marrow edema (BME) and collateral ligament pathology. The patients were divided into groups according to the ACL injury pattern. The prevalence of injury of the anatomical structures between groups was examined. Results: MRI scans of 152 patients (152 knees) were evaluated. The mean age of the patients was 28.5±8.6 (range, 18-55). 138 patients were male and 14 were female. Complete ACL injury was detected in 127 (83.6%) patients confirmed by MRI and arthroscopic procedure and partial ACL injury was detected in 25 (16.4%) patients confirmed by MRI. 90 (59.2%) patients had an ALL injury, 87 (57.2%) had an iliotibial band injury, 82 (53.9%) patients had a Kaplans fiber injury, 53 (34.9%) patients had a meniscal injury, 99 (65.1%) patients had BME and 70 (46.1%) patients had a collateral ligament injury. In the complete ACL injury group, the ratio of ALL, iliotibial band, Kaplan fiber, meniscal injury, BME, collateral ligament injury was significantly higher than the partial ACL injury group (p 0.05). Conclusion: The prevalence of injury in at least one anatomic structure of ALC was significantly higher in patients with a complete ACL injury (73.2%) than those with partial ACL injury (32%) at our institution. This study demonstrated that ALC injuries were statistically higher as well as meniscal injuries, BME, collateral ligament injuries after complete ACL injury compared to partial ACL injury.
Keywords: Anterolateral complex; anterior cruciate ligament; anterolateral ligament; anotomy; knee; Iliotibial band; imaging